Perbedaan Intelligence Quotient (IQ) Anak Obes dan Tidak Obes Usia Sekolah Dasar di SD Kristen Manahan Surakarta - Wibawati, Magdalena; Karini, Suci Murti; Widardo, . (Nexus Kedokteran Komunitas, 2013)
Background: Prevalence of obesity has increased over the last 20 years and become worldâs health problems. Obesity in children may cause medical and psychosocial consequences, which can influence their Intelligence Quotient. The aim of this research is to determine whether the difference of Intelligence Quotient existed in obese and non-obese children in Manahan Christian Primary School Surakarta. Methods: This research is an analytic observational study with cross sectional approach. Sample was collected by simple random sampling. Based on the anthropometric measurement of 2nd until 5th grade students in Manahan Christian Primary School Surakarta, 30 samples were collected for each group (obese and non-obese children). Intelligence Quotient test were performed using Culture Fair Intelligence Test (CFIT) 2A by the students who become research sample.Â Data were analyzed with unpaired t-test by Statistical Product and Serve Solution (SPSS) 21 for Mac. Results: Mean score of Intelligence Quotient in the obese children is 105.29, while in the non-obese children is 105.82. Result of unpaired t test showed the probability of 0.849 (p > 0.05). It means the significance value of the difference between the two groups was not significant. Conclusions: There is no difference of Intelligence Quotient (IQ) between obese and non-obese children in Manahan Christian Primary School Surakarta. Keywords: Intelligence Quotient, obese children, non-obese childrenÂ